2009
DOI: 10.1042/bst0370727
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional restraints in the evolution of protein families and superfamilies

Abstract: Divergent evolution of proteins reflects both selectively advantageous and neutral amino acid substitutions. In the present article, we examine restraints on sequence, which arise from selectively advantageous roles for structure and function and which lead to the conservation of local sequences and structures in families and superfamilies. We analyse structurally aligned members of protein families and superfamilies in order to investigate the importance of the local structural environment of amino acid resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…One of the prospective ways to reveal these relations is an analysis of 3-dimensional structures of RNA and RNA-protein complexes. This approach has been successfully used for analysis of conformational features of interacting surfaces in proteins (e.g., (Gong et al, 2009)). …”
Section: Introductionmentioning
confidence: 99%
“…One of the prospective ways to reveal these relations is an analysis of 3-dimensional structures of RNA and RNA-protein complexes. This approach has been successfully used for analysis of conformational features of interacting surfaces in proteins (e.g., (Gong et al, 2009)). …”
Section: Introductionmentioning
confidence: 99%
“…Over the last half century, studies of the three-dimensional structures of proteins have revealed how a protein's three-dimensional structure relates to its biochemical function. Gong et al [16] show how different locations in the three-dimensional structure impose different constraints on which amino acid substitutions can be tolerated in order to preserve structure and/or function (see pp. 727-733).…”
Section: What Are the Constraints On Protein Evolution?mentioning
confidence: 99%
“…Interestingly, the 16th residue, which corresponds to a small aminoacid, is occupied in mammalian insulins by a glycine, with a positive main-chain torsion angle that allows the chain to change direction sharply. On the other hand, the positions involved in dimer formation are occupied by hydrophobic residues in all species except the hystricomorphs (Gong et al, 2009).…”
Section: Insulin Domain Log-likelihoodmentioning
confidence: 99%